2021
DOI: 10.3892/mmr.2021.11865
|View full text |Cite
|
Sign up to set email alerts
|

IL-32 exacerbates adenoid hypertrophy via activating NLRP3-mediated cell pyroptosis, which promotes inflammation

Abstract: Adenoid hypertrophy (AH) is a common pediatric disease caused by inflammatory stimulation. The pro-inflammatory cytokine IL-32 has been reported to promote airway inflammation and also be involved in the pyroptosis pathway. However, whether IL-32 can contribute to AH by mediating pyroptosis remains to be elucidated. The present study aimed to investigate the role of IL-32 in AH and determine the potential underlying mechanisms. Adenoid tissues were collected from healthy children and children with AH, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Meanwhile, pyroptosis‐resistant genes like FASN, 53 GPX4 54 were also upregulated in nutlin‐3 treated LN229 (Figure S10E), and the expression of pyroptosis sensitivity genes like IL32 55 and PTX3 56 was increased in nutlin‐3‐treated T98G (Figure S10F). Moreover, the expression of pyroptosis sensitivity genes like the GBP family, 57 NLRP3, IL‐1β, and CASP14 58 was decreased in nutlin‐3 treated LN229 (Figure S10G).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, pyroptosis‐resistant genes like FASN, 53 GPX4 54 were also upregulated in nutlin‐3 treated LN229 (Figure S10E), and the expression of pyroptosis sensitivity genes like IL32 55 and PTX3 56 was increased in nutlin‐3‐treated T98G (Figure S10F). Moreover, the expression of pyroptosis sensitivity genes like the GBP family, 57 NLRP3, IL‐1β, and CASP14 58 was decreased in nutlin‐3 treated LN229 (Figure S10G).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we demonstrate that LDR preirradiation can enhance HDR-induced pyroptosis. More intriguingly, HDR also induced the secretion of IL-32 and TNF-α, which can induce the onset of pyroptosis, 43,44 and LDR pre-irradiation also enhanced the HDR-induced secretion of both. Most importantly, we proved that after NLRP3 expression was reduced by using NLRP3-siRNA or NLRP3 inhibitors, pyroptosis-related protein expression was no longer increased after irradiation, and LDR no longer enhanced the proliferation inhibition of tumor cells by HDR, which further confirmed that pyroptosis is the mechanism by which LDR enhances the tumor-suppressive effect of HDR.…”
Section: Discussionmentioning
confidence: 95%
“…For example, upregulation of interleukin (IL)-32 in adenoid tissue was shown, which might have a potential effect on AH progression through stimulation of proinflammatory cytokines production as well as pyroptosis in human nasal epithelial cells mediated by NOD1/2/TLR4/NLRP3 pathway (nucleotide-binding oligomerization domain-containing protein/toll-like receptor/nucleotide-binding oligomerisation domain, leucine-rich repeat and pyrin domain-containing proteins). 26 Moreover, elevated levels of proinflammatory cytokines such as high-sensitivity C reactive protein, IL-1 and IL-10, interferon-γ (IFN-γ), TNF-α (tumor necrosis factor α) as well as intercellular adhesion molecule-1 in children with AH have been observed. 27 Genetic factors include, among others, polymorphisms in genes coding: SCGB1D4 (IFN-γ stimulated cytokine regulating chemotaxis of immune cells), TLR2 and TLR4 (play a key role in the regulation of the immune system through recognition of molecular patterns commonly found on pathogens (pathogen-associated molecular patterns)).…”
Section: Pathogenesis Of Ahmentioning
confidence: 99%
“…Among immune disturbances, altered production of cytokines is described. For example, upregulation of interleukin (IL)-32 in adenoid tissue was shown, which might have a potential effect on AH progression through stimulation of proinflammatory cytokines production as well as pyroptosis in human nasal epithelial cells mediated by NOD1/2/TLR4/NLRP3 pathway (nucleotide-binding oligomerization domain-containing protein/toll-like receptor/nucleotide-binding oligomerisation domain, leucine-rich repeat and pyrin domain-containing proteins) 26. Moreover, elevated levels of proinflammatory cytokines such as high-sensitivity C reactive protein, IL-1 and IL-10, interferon-γ (IFN-γ), TNF-α (tumor necrosis factor α) as well as intercellular adhesion molecule-1 in children with AH have been observed 27.…”
Section: Pathogenesis Of Ahmentioning
confidence: 99%